1960
DOI: 10.3402/tellusa.v12i1.9341
|View full text |Cite
|
Sign up to set email alerts
|

The Yearly Circulation of Chloride and Sulfur in Nature; Meteorological, Geochemical and Pedological Implications. Part II

Abstract: IV. The yearly circdation of sea d t s between continents and the oceans I . IntroductionThe yearly global circulation of sea salts between continents and oceans can be estimated in several ways. One is by actually measuring the yearly amounts brought down on land by available techniques. It is clear from the preceding chapter that this is technically difficult. It is easy to collect precipitation and analyse it for various sea salt constituents but it is more difficult to estimate how much is brought down by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

1966
1966
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 48 publications
1
53
0
1
Order By: Relevance
“…3 (16.9€1.2 atoms m -2 s -1 ), it is possible to estimate that 26€11% of the total mean 36 Cl fallout for the continental United States occurs as dry deposition. This is in good agreement with Eriksson (1960) and Bentley et al (1986) who suggested that dry fallout should be approximately 23% of total deposition. Taking the relative fraction of dry deposition to be 26€11%, the total mean flux of 36 Cl over the United States is 30.5€7.0 atoms m -2 s -1 .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…3 (16.9€1.2 atoms m -2 s -1 ), it is possible to estimate that 26€11% of the total mean 36 Cl fallout for the continental United States occurs as dry deposition. This is in good agreement with Eriksson (1960) and Bentley et al (1986) who suggested that dry fallout should be approximately 23% of total deposition. Taking the relative fraction of dry deposition to be 26€11%, the total mean flux of 36 Cl over the United States is 30.5€7.0 atoms m -2 s -1 .…”
Section: Resultssupporting
confidence: 81%
“…Most of the chloride that is deposited on the continent originates as particulates released to the atmosphere from the oceans (Eriksson 1960;Semonin and Bowersox 1982;Li 1992;Simpson and Herczeg 1994). Once chloride is suspended in the atmosphere, it can be carried inland by winds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy could show that emissions of NO X are not merely the source of dust nitrate. Previous studies repeatedly reported that the formations of particulate sulfate and nitrate on sea salt particles (Eriksson 1959;McInnes et al 1994) and dust particles enhanced the production of particulate sulfate and nitrate in the downstream atmosphere (Nishikawa et al 1991;Dentener 1996;Tang 2004). The sea is about 2-3 km from the tested area, which is where the particles could have originated from, and the wind could have induced the transportation.…”
Section: Source Of Chemical Constituents Of Dust Fallmentioning
confidence: 99%